Do lifestyle interventions work in developing countries? Findings from the Isfahan Healthy Heart Program in the Islamic Republic of Iran - Nizal Sarrafzadegan; Roya Kelishadi; Ahmad Esmaillzadeh; Noushin Mohammadifard; Katayoun Rabiei; Hamidreza Roohafza; Leila Azadbakht; Ahmad Bahonar; Gholamhossein Sadri; Ahmad Amani; Saeid Heidari; Hossein Malekafzali
OBJECTIVE: To assess the effects of a comprehensive, integrated community-based lifestyle intervention on diet, physical activity and smoking in two Iranian communities. METHODS: Within the framework of the Isfahan Healthy Heart Program, a community trial was conducted in two intervention counties (Isfahan and Najaf-Abad) and a control area (Arak). Lifestyle interventions targeted the urban and rural populations in the intervention counties but were not implemented in Arak. In each community, a random sample of adults was selected yearly by multi-stage cluster sampling. Food consumption, physical exercise and smoking behaviours were quantified and scored as 1 (low-risk) or 0 (other) at baseline (year 2000) and annually for 4 years in the intervention areas and for 3 years in the control area. The scores for all behaviours were then added to derive an overall lifestyle score. FINDINGS: After 4 years, changes from baseline in mean dietary score differed significantly between the intervention and control areas (+2.1 points versus -1.2 points, respectively; P < 0.01), as did the change in the percentage of individuals following a healthy diet (+14.9% versus -2.0%, respectively; P < 0.001). Daily smoking had decreased by 0.9% in the intervention areas and by 2.6% in the control area at the end of the third year, but the difference was not significant. Analysis by gender revealed a significant decreasing trend in smoking among men (P < 0.05) but not among women. Energy expenditure for total daily physical activities showed a decreasing trend in all areas, but the mean drop from baseline was significantly smaller in the intervention areas than in the control area (-68 metabolic equivalent task (MET) minutes per week versus -114 MET minutes per week, respectively; P < 0.05). Leisure time devoted to physical activities showed an increasing trend in all areas. A significantly different change from baseline was found between the intervention areas and the control area in mean lifestyle score, even after controlling for age, sex and baseline values. CONCLUSION: The results suggest that community-based lifestyle intervention programmes can be effective in a developing country setting.